Social Entrepreneurship and Tourism : Philosophy and Practice - Sheldon, Pauline J.; Daniele, Roberto (Springer International Publishing : Imprint : Springer, 2017)
This volume explores the links between the rapidly growing phenomenon of social entrepreneurship (SE) and the international tourism and hospitality industry. This unique industry is particularly ripe for transformation by SE and the book's authors delve deeply into the reasons for this. The book has three parts. The first creates a conceptual and theoretical framework for understanding the uniqueness of SE in the tourism context. The second examines different communities of practice where SE is being applied in tourism. The third is a rich collection of case studies from eight countries where tourism SE is already having an impact. The book's authors address the topic from many different angles, disciplinary backgrounds and geographic areas. Many case study authors are practicing social entrepreneurs who share their successes, challenges and experience with tourism-related projects. The book also proposes a research agenda and educational programmatic changes needed to support tourism SE. As these are developed, tourism SE will bring innovation to destinations, transformation of their economic and social structures, and contribution to a better world. The book has many insights and resources for scholars and practitioners alike to usher in this transformation
Keywords: Tourism -- Management.; Hospitality industry -- Management.; Social entrepreneurship.; Nature conservation.; Environmental economics.; elektronické knihy; electronic books